Personal potential as a basis of healthcare workers' professional activity - Москальова, Алла; Василига, Ольга (Київський національний університет імені Тараса Шевченка, 2019)
The article provides a theoretical analysis of various approaches to studying the concept of "personal potential" of an individual as a psychological phenomenon. The paper analyzes the current state of research of different approaches to the study of the personal potential of the individual, in particular the psychological characteristics of medical professionals, and investigates the psychological features of the personal capacity of medical professionals and their impact on professional activity. The personal potential of the individual is analyzed through the prism of concepts of self-realization, integral system of individual psychological features, system of internal restorative resources and dynamic psychological system. An analysis of the work of Ukrainian psychologists on the problem of researching the personal potential of medical professionals is given. On the basis of theoretical analysis, the concept of personal potential of medical workers is operationalized through the notion of vital, personal meaning of professional activity. It clarifies the specificity of healthcare workers' professional activity in the context of healthcare reform and determines the importance of personal potential in it. The article also focuses on psychological characteristics of healthcare workers' personal potential and their impact on the professional activity. The article identifies the spheres of realization of medical workers in their professional activity through the purpose of activity, the pursuit of self-improvement, as well as through professional, psychological, unlocking their potential. The study determined the degree of motivational self-regulation, styles of self-regulation and self-esteem of mental states of health workers. The psychological peculiarities of the personality potential of the personality affecting the professional activity of medical workers are revealed. The main obstacles to the disclosure of the personal potential of health care workers have been identified. Based on the analysis, recommendations were made regarding the prospects of further research into the personal potential of healthcare professionals.

У статті здійснено теоретичний аналіз різних підходів до вивчення поняття "особистісний потенціал" особистості як психологічного феномену. З'ясовано специфіку професійної діяльності медичних працівників за умов реформування медичної галузі. Визначено роль особистісного потенціалу у професійній діяльності медичних працівників. Виявлено психологічні особливості особистісного потенціалу медичних працівників та їхній вплив на професійну діяльність.
Особистісний потенціал як основа професійної діяльності медичних працівників
Keywords: особистісний потенціал; професійна діяльність; медичний працівник; особистісний потенціал медичного працівника; personal potential; professional activity; healthcare worker; healthcare worker's personal potential